Acute promyelocytic leukemia lacking t(15;17): Molecular evidence of atypical PML/RAR-α transcriptional variant by gene sequencing - Đorđević Vesna; Tošić Nataša; Denčić-Fekete Marija; Virijević Marijana; Jovanović Jelica; Jaković Ljubomir; Kraguljac-Kurtović Nada; Bogdanović Andrija; Kostić Tatjana; Pavlović Sonja (Vojnosanitetski Pregled)
Introduction. The accurate diagnosis of acute promyelocytic leukemia (APL), not only on the morphological and clinical, but also on the molecular level, is very important for application of targeted therapies. Case report. A 62- year-old woman presented with APL. By using conventional cytogenetic analysis as well as applying the fluorescence in situ hybridization (FISH) analysis it has not been possible to confirm the presence of t(15;17) in the presented patient. Using reverse transcriptase polymerase chain reaction (RT-PCR) two atypical promyelotic leukemia/ retinoic acid receptor alpha (PML/RAR-α) fusion transcripts were identified. Both detected transcripts were isoforms. The larger transcript was in-frame, coding for functional aberrant PML/RAR-α protein, while the shorter transcript was an out-of-frame. Conclusion. Our study highlights the need for the application of molecular methodology in daily clinical practice. Precise characterization of PML/RAR-α fusion transcript creates a basis for identifying rare individual cases that require special caution when treating such patients. To our knowledge this is only the fifth case of atypical PML/RAR-α transcript containing full PML exon 7a, and among them the only one that was cytogenetically cryptic and FISH negative. All of the herein presented cases had lethal outcome. Therefore, our findings with the additional review of the literature, emphasizes the importance of detailed identification of atypical PML/RAR-α fusions, not only for the purpose of knowing their role in leukemogenesis, but also for the assessment of the impact that they can have on the outcome of the treatment.